2022
DOI: 10.3390/pharmaceutics14020436
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Components in Edible Mushrooms on Diabetes Mellitus Treatment

Abstract: Mushrooms belong to the family “Fungi” and became famous for their medicinal properties and easy accessibility all over the world. Because of its pharmaceutical properties, including anti-diabetic, anti-inflammatory, anti-cancer, and antioxidant properties, it became a hot topic among scientists. However, depending on species and varieties, most of the medicinal properties became indistinct. With this interest, an attempt has been made to scrutinize the role of edible mushrooms (EM) in diabetes mellitus treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 92 publications
(70 reference statements)
1
7
0
Order By: Relevance
“…We succeeded in proving our primary hypothesis that the daily consumption of the snack regulates glucose levels compared with the control group. Our findings are in accordance with the existing literature, as it has been shown that mushrooms possess an antidiabetic effect mainly due to their polysaccharide content [ 31 ] and by increasing glucokinase activity [ 32 ]. P. ostreatus exhibits similar effects, with a 7-day consumption of a cooked mushroom meal in exchange for vegetables to hospitalized patients with insulin resistance, resulting in a 22% reduction in fasting glucose [ 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…We succeeded in proving our primary hypothesis that the daily consumption of the snack regulates glucose levels compared with the control group. Our findings are in accordance with the existing literature, as it has been shown that mushrooms possess an antidiabetic effect mainly due to their polysaccharide content [ 31 ] and by increasing glucokinase activity [ 32 ]. P. ostreatus exhibits similar effects, with a 7-day consumption of a cooked mushroom meal in exchange for vegetables to hospitalized patients with insulin resistance, resulting in a 22% reduction in fasting glucose [ 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…The growth of milk mushroom species (Calocybe indicia), which are high in vitamins and calcium, and have nutraceutical, pharmaceutical, bioremediation and biodegradable properties, has continued and gained momentum in recent years [18]. In addition, mushrooms have more than 100 therapeutic properties, with their primary medical applications being for detoxification, antibacterial, immunomodulation, antifungal, antiviral, antiparasitic, antitumor, antiallergic, antioxidant, and anticholesterolemic effects [19]. In particular, the presence of biologically active substances that inhibit enzymes can contribute to antidiabetic activity.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, research into the precise molecular mechanism that can reveal their anti-diabetic potential is required. Animal studies have provided the most conclusive proof of medicinal mushrooms’ therapeutic properties [ 27 ].…”
Section: Challengesmentioning
confidence: 99%
“…In addition to homoglucans (β-1, 3 glucan), heteroglycans, heterogalactans, and heteromannans, mushrooms also contain other structural polysaccharides. By inhibiting glucosidase, supporting the functions of glucose transporter 4, and lowering inflammatory markers, these polysaccharides and terpenoids (secondary metabolites) play a crucial role in glucose homeostasis and enhance insulin resistance and lipid metabolism [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%